NON-INVASIVE ELECTROPHYSIOLOGICAL MARKERS OF HIGHER RISK FOR FATAL OUTCOMES IN DILATION CARDIOMYOPATHY PATIENTS - A. V. Sedov; D. A. Tsaregorodtsev; V. A. Sulimov (Российский кардиологический журнал)
Dilation cardiomyopathy (DCMP) remains a disease with poor prognosis.Aim. To study the importance of risk stratification improvement for fatal outcomes, especially sudden cardiac death (SCC), with the aim for on-time prevention procedures, as the previously proposed non-invasive electrophysiological predictors — heart rhythm turbulence (HRT) and variability (HRV), microvolt alternation of T wave (mTWA), deceleration capacity (DC) and acceleration capacity (AC) in DCMP are not studied well enough.Material and methods. During 4 years there was follow-up of 54 DCMP patients and sinus rhythm at the age 42 [30;58] year-old (36 males) and control group — 54 persons with no cardiovascular pathology (32 males, mean age 47 [27;64] y.o.). At baseline the Holter monitoring was done, of ECG with HRV, HRT, DC, AC, mTWA assessment, and echocardiography. Patients took standard treatment of chronic heart failure (CHF); part of cardioverter-defibrillator (CD) implanted was 18,5%.Results. Mean ejection fraction (EF) in the main group was 32% [22;38], signs of CHF had 93% of patients. Those with DCMP differed from the main group by significantly lower values of SDNN, pNN50, DC, TO, TS, higher AC and mTWA in early morning. During 4 years there was 1 SCD, and 7 died from CHF progression; there was 1 adequate shock in CD patient (totally 9 deaths). Comparing to those survived, died patients had had lower EF, HRV, DC, maximal mTWA values, higher end diastolic volume, CHF class, AC, mTWA, number of episodes of non-sustained ventricular tachycardia (nsVT) in morning. Under monofactorial analysis there was significant influence on fatal outcome risk of the following (in order of declining significance): EF (odds ratio (OR) 32), SDNN (OR 21), DC (OR 9), AC (OR) 7, pNN50 (OR 6), nsVT (OR 5,2; p=0,05). In multifactor analysis the only independent predictor of fatal outcomes was the decrease of EF of the left ventricle less than 26% (sensitivity 80%, specificity 90%).Conclusion. DCMP patients, comparing to persons with no cardiovascular pathology, have decreased HRV and DC, increased AC, more common pathological HRT, increase of mTWA in early morning, and in those died these specifics was more prominent. In monofactor analysis the non-invasive electrophysiological predictors associated with poor DCMP prognosis, were AC, SDNN DC, pNN50, nsVT. However the most significant and the only independent predictor of fatal outcomes in DCMP patients is the decrease of EF. If to apply the EF less than 26% as a criteria of high risk, it predicts the 32 times increase of fatal outcomes risk with sensitivity 80% and specificity 90%.